the nth term of a sequence is given by this formula:

nth term = 62 - 5n

Find an expressipn, in terms of n, for the sum of the nth term and (n+1)th term of the sequence. thanks

Printable View

- Oct 28th 2008, 12:40 PMabey_27INTEGER SEQUENCES
the nth term of a sequence is given by this formula:

nth term = 62 - 5n

Find an expressipn, in terms of n, for the sum of the nth term and (n+1)th term of the sequence. thanks - Oct 28th 2008, 01:28 PMSoroban
Hello, abey_27!

It seems simple enough . . . Exactly where is your difficulty?

Quote:

The $\displaystyle n^{th}$ term of a sequence is given by: .$\displaystyle a_n \:=\:62-5n$

Find an expression, in terms of $\displaystyle n$,

for the sum of the $\displaystyle n^{th}$ term and $\displaystyle (n+1)^{th}$ term of the sequence.

We have:. $\displaystyle \begin{array}{ccc}a_n &=& 62 - 5n \\

a_{n+1} &=& 62-5(n\!+\!1) \end{array}$

Therefore: .$\displaystyle a_n + a_{n+1} \;=\;[62-5n] + [62-5(n+1)] \;=\;119 - 10n$

- Oct 28th 2008, 01:43 PMabey_27
i didnt really understand what it meant by 'sum of the nth term', so is that simply just the formula nth term= 62-5n ?